2012
DOI: 10.1136/tobaccocontrol-2011-050200
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco industry denormalisation as a tobacco control intervention: a review

Abstract: Objective To conduct a review of research examining the effects of tobacco industry denormalisation (TID) on smoking-related and attitude-related outcomes. Methods The authors searched Pubmed and Scopus databases for articles published through December 2010 (see figure 1). We included all peer-reviewed TID studies we could locate that measured smoking-related outcomes and attitudes toward the tobacco industry. Exclusion criteria included: non-English language, focus on tobacco use rather than TID, perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 85 publications
1
97
0
1
Order By: Relevance
“…A number of campaigns referenced unhealthy foods (21 %) or SSB (18 %), although implications of the food industry in rising obesity rates varied in explicitness. Among tobacco-prevention campaigns, those highlighting the role of industry have been associated with effectiveness (54) . Other campaign elements may not be optimal.…”
Section: Discussionmentioning
confidence: 99%
“…A number of campaigns referenced unhealthy foods (21 %) or SSB (18 %), although implications of the food industry in rising obesity rates varied in explicitness. Among tobacco-prevention campaigns, those highlighting the role of industry have been associated with effectiveness (54) . Other campaign elements may not be optimal.…”
Section: Discussionmentioning
confidence: 99%
“…6 There is some evidence that TID is linked with reductions in smoking prevalence and initiation and increased quit intentions. 7 There remains a reluctance however to include TID within tobacco control in most countries, possibly due to a lack of political will, fear of litigation or a dearth of country-specific research. 8 To inform a TID campaign, and indeed give some indication as to whether this may be of value, an important starting point is to gauge public awareness of tobacco 5 companies and perceptions of their practices and values, as well as level of support for further regulation of tobacco companies.…”
Section: Introductionmentioning
confidence: 99%
“…7 A study in Russia in 2007 found that on one hand the tobacco industry was perceived by only 3.5% of adults as unethical, while on the other only 10.1% believed that they did not bribe politicians and officials. With respect to these seemingly divergent findings, the authors note that due to Russia's poor performance on corruption indexes it may be that consumers do not view the tobacco industry as any more unethical than other industries, with bribery perceived as commonplace in all.…”
Section: Introductionmentioning
confidence: 99%
“…50(p1840) Though the population-level success of tobacco denormalization is widely accepted, [3][4][5][6][7][8] it remains unclear if tobacco denormalization strategies also alleviate health inequities for sexual and gender minorities. We believe that a focus on stigma should be paramount in research on tobacco, particularly when the stigmatization of tobacco is commonplace and arguably reinforced by public health policies, and when disparities in tobacco use prevalence fall on the most stigmatized.…”
Section: -58mentioning
confidence: 99%
“…Studies suggest that tobacco denormalization is a successful populationlevel approach for reducing the prevalence of smoking. [3][4][5][6][7][8] For example, Alamar and Glantz 9 found that increasing the social unacceptability of smoking is an effective policy tool to reduce cigarette smoking, with results revealing that for every 10% increase in the social unacceptability of tobacco index, there would be an associated 3.7% drop in cigarette consumption.…”
mentioning
confidence: 99%